Pengalaman Perawat Melaksanakan Pengkajian Keperawatan Kegawatdaruratan - I Made Sukma Wijaya; Ahsan Ahsan; Kumboyono Yono (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2014)
The aims of this study is to explore the experiences of nurses perform nursing emergency assessment in the triage room. This study used a qualitative research design with interpretive phenomenological approach. Participant of this study as many as eigth people who work at triage room emergency Sanglah Hospital Denpasar. All participants have been work more than three years in the emergency room that conducted indepth interviews to explore their experiences. Data from interviews were transcripts and analyzed using Dikelman which resulted three major themes in the experience of nurses perform nursing assessment that is material (initial and further assessment), data sources (primer and secondary data) and limitations (health provider and patient aspects).